Pengaruh Viral Marketing, Flash Sale 12.12, dan Tagline Gratis Ongkos Kirim Terhadap Keputusan Pembelian Barang Di Marketplace Shopee (Studi Kasus Mahasiswa FEB Unisma Angkatan 2019) - Prapti Komala Sawitri; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study examines the effect of Viral Marketing, Flash Sale 12.12, and the Free Shipping Tagline on purchasing decisions for goods on the Shopee marketplace. The method of this research is explanatory research with quantitative methods. The 2019 class of FEB Islamic University of Malang served as the study's population. This study used a nonprobability sampling method with a purposive sampling technique, collecting a sample of 80 respondents using a Google form following the formula used; the Malhotra formulated the purpose of this SPSS 25 data analysis is to examine the effect of viral marketing, flash sales 12.12, and the free shipping tagline on purchasing decisions. Viral marketing had a positive and partially significant influence on buying decisions in this study, flash sale 12.12 had a slightly optimistic and substantial impact on buying decisions, and the free delivery slogan had a positive and partially significant effect on buying decisions. The influence of viral marketing, flash sales 12.12, and the free shipping tagline on the decision to buy goods in the shopee marketplace, the case study of FEB students at the Islamic University of Malang was 61.5%. Other variables influenced the remaining 38.5% not in the study. Keywords: Viral Marketing, Flash Sale 12.12, and Free Shipping Tagline